THE USE OF ROUND ROBIN TECHNIQUE TO IMPROVE THE READING COMPREHENSION AT THE EIGHT YEAR STUDENTS’ OF SMP NEGERI 1 SUPPA KAB PINRANG - Siti hasrina; Nanning; Mujahidah (Prodi Tadris Bahasa Inggris STAIN Parepare (IAIN Parepare), 2018)
To solve problem in the learning process, the researcher applied an innovative technique to improve the students? reading comprehension. The researcher offered round robin technique as a technique to teach reading. The objective of the research are expected to find out whether or not the use Round Robin technique be able to improve the students? reading comprehension and to know how is the students? response toward the implementation of Round Robin technique in reading comprehension of the eight year students? at SMPN 1 Suppa Kab.Pinrang.The result of this research was expected to be useful information in the English teaching and learning process especially in the reading teaching. This research applied pre-experimental method, with two group pre-test and post-test design. The samples of the research were consisted of 23 students from six classes taken from the population at the eight year students of SMP Negeri 1 Suppa Kab.Pinrang second semester in Academic Year 2017/2018.The result of the data analysis showed that the students? reading comprehension was improved . It could be showed from The result of the t-obtained value (2.391) was higher than t-table value (2.074). Those indicated that H0 was rejected and Ha was accepted. It meant that the students? reading comprehension was able to increase by using round robin technique.